IMPROVING B1-LEVEL ESP LEARNERS’ ORAL FLUENCY THROUGH GAME-BASED LEARNING: A QUASI-EXPERIMENTAL STUDY (American Journal of Interdisciplinary Research and Development, 2026)
This research examines the potential of game-based learning to enhance the oral fluency of B1-level English for Specific Purposes (ESP) learners. The study is predicated on the premise that fluency is cultivated most successfully when learners are given frequent chances to use language in a meaningful, spontaneous manner, and within communicative contexts. During a ten-week intervention, the experimental group engaged in fluency-oriented communicative games, while the control group participated in conventional speaking practice grounded on more structured classroom activities. The findings indicate that the experimental group attained superior improvements in speech pace, reduced pause frequency, and enhanced total fluency scores compared to the control group. Moreover, students engaged in game-based activities were more inclined to maintain discourse and reply with greater spontaneity during interactions. These results indicate that communicative games provide optimal circumstances for the advancement of oral fluency by promoting the recurrent use of known language within a controllable communicative context. The research corroborates the perspective that fluency is enhanced not just by linguistic knowledge, but also by active engagement, self-assurance, and contextually relevant speaking practice. Consequently, game-based learning is considered an effective pedagogical method in ESP speaking sessions.